Profiles for long non-coding RNAs in ovarian granulosa cells from women with PCOS with or without hyperandrogenism. Issue 5 (November 2018) - Jin, Li; Yang, Qian; Zhou, Chengliang; Liu, Lanxin; Wang, Huihui; Hou, Min; Wu, Yimei; Shi, Fengtao; Sheng, Jianzhong; Huang, Hefeng
Highlights: PCOS patients with hyperandrogenism displayed 3000 and 1030 differentially expressed lncRNAs as compared to Control and PCOS patients without hyperandrogenism. CRHBP remains consistently the up-regulated lncRNA in PCOS with hyperandrogenism whether compared to PCOS without hyperandrogenism or Control patients. Co-expression analysis suggests differentially expressed lncRNAs in PCOS patients with hyperandrogenism probably play their regulatory role by interacting with transcription factor including YY1 and SIX5. GO and Pathway analysis indicated that differential lncRNAs probably cause mitochondrial changes in PCOS with hyperandrogenism. Abstract: Research question: What is the expression pattern of long non-coding RNAs (lncRNA) in ovarian granulosa cells of women with polycystic ovary syndrome (PCOS) with or without hyperandrogenism? Design: Microarray screening of lncRNA was conducted in ovarian granulosa cells collected from women with PCOS with hyperandrogenism (PCOS-T) or without hyperandrogenism (PCOS-N) and control participants, with four samples in each group. This was followed by hierarchy clustering, gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses. Several candidate lncRNA were randomly selected for quantitative polymerase chain reaction validation in another 54 patients. To predict the regulatory effect of lncRNA on hyperandrogenism, a co-expression network was plotted using differentially hexpressed lncRNA with statistical significance (≥ twofold; P < 0.05) in PCOS-T compared with PCOS-N. Results: A total of 3000 and 1030 differentially expressed lncRNA (≥ twofold change) were detected in PCOS-T compared with control and PCOS-N, respectively. A total of 1361 differentially expressed lncRNA were detected in PCOS-N compared with controls. Corticotropin releasing hormone binding protein is consistently the up-regulated lncRNA with the highest fold-change in PCOS-T compared with either control or PCOS-N. Gene ontology and pathway analysis showed that dysregulated lncRNA in PCOS-T have a regulatory role in mitochondrial function by interacting with transcription factors such as YY1 and SIX5. Conclusions: The expression patterns of lncRNA in women with PCOS were ascertained by microarray. Many lncRNA were differentially expressed in PCOS-T compared with PCOS-N, suggesting that they may play a key role in steroid genesis and metabolism.